WCRF/AICR recommendation adherence and breast cancer incidence among postmenopausal women with and without non‐modifiable risk factors. Issue 11 (3rd February 2016) - Nomura, Sarah J.O.; Inoue‐Choi, Maki; Lazovich, DeAnn; Robien, Kim
Abstract : Taller height, family history of breast cancer, greater number of years of potential fertility and nulliparity are established non‐modifiable risk factors for postmenopausal breast cancer. Greater adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) diet, physical activity and body weight recommendations has previously been shown to be associated with lower breast cancer risk. However, no prior studies have evaluated whether women with non‐modifiable risk factors receive similar benefits from recommendation adherence compared to women without these risk factors. In the Iowa Women's Health Study prospective cohort, we investigated whether associations of WCRF/AICR recommendation adherence differed by the presence/absence of non‐modifiable breast cancer risk factors. Baseline (1986) questionnaire data from 36, 626 postmenopausal women were used to create adherence scores for the WCRF/AICR recommendations (maximum score = 8.0). Overall and single recommendation adherence in relation to breast cancer risk ( n = 3, 189 cases) across levels of non‐modifiable risk factors were evaluated using proportional hazards regression. Mean adherence score was 5.0 points (range: 0.5–8.0). Higher adherence scores (score ≥6.0 vs . ≤3.5, H R = 0.76, 95% CI = 0.67–0.87), and adherence to the individual recommendations for body weight and alcohol intake were associated with a lower breast cancer incidence. While not statistically significant among women with more non‐modifiable risk factors (score ≥6.0 vs . ≤3.5, H R = 0.76, 95% CI = 0.36–1.63), hazard ratios were comparable to women with the no non‐modifiable risk factors (score ≥6.0 vs . ≤3.5, H R = 0.74, 95% CI = 0.49–0.93) ( p ‐interaction = 0.57). WCRF/AICR recommendation adherence is associated with lower breast cancer risk, regardless of non‐modifiable risk factor status. Abstract : What's new? Women with non‐modifiable risk factors for breast cancer may be inclined to alter their diet and physical activity to reduce their risk. However, it remains uncertain whether measures to improve health actually benefit these women. In this study, women who adhered to World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR) recommendations on alcohol intake and body weight were found to have a reduced risk of breast cancer incidence, regardless of the presence of non‐modifiable risk factors. The findings suggest that postmenopausal breast cancer risk may be lowered through adherence to the 2007 WCRF/AICR cancer prevention guidelines.